Ceratocystis paradoxa associated mycotoxin – deterring bud germination in sugarcane - and SRIKANT KULKARNI, K.B. YADAHALLl*, S.S. ADIVER (Indian Phytopathology, 2007)
The major cause of rotting of sugarcane setts is invasion by Ceratocystis paradoxa, an ascomycetous fungus. To arrest this process of rotting of the planted setts and to control further proliferation of the fungus, it becomes imperative to study the mechanism of invasion and the chemical compounds released (toxins) so as to break the defense mechanism of the host plant. The seed germination bio-assay revealed that tomato seeds had least germination per cent (20.50%) in culture filtrate, while all other crop seeds had higher germination per cent. The toxin was identified to be ethyl acetate. Assessment of effect of ethyl acetate on the sett germination, shoot and root length and number of roots per node, revealed they being affected drastically.